THE IMPORTANCE OF EDUCATIONAL PRACTICE IN THE UPBRINGING OF FUTURE PRIMARY SCHOOL TEACHERS - Ahmedova Gulnoza Zoir’s daughter (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes the results of studying and analyzing the experience of organizing and conducting pedagogical practices of students based on the competence approach. The purpose of the study is to theoretically substantiate the need to improve pedagogical practice in the professional development of future teachers. The current state of the research problem has led to the improvement of scientific and methodological support for the pedagogical practice of students-future teachers, primary classes. Pedagogical practice is considered by us as the main component of professional training of students. Thus, the conducted research allowed us to formulate a conclusion that in planning, content and organization of pedagogical practices in order to implement a competency-based approach, along with taking into account the necessary factors, special attention should be paid to the individual characteristics of future primary school teachers in order to build their individual development trajectory in professional formation.